Knowledge, attitudes and practices in biosafety and biosecurity in medical biology laboratories in Togo, 2021 - Halatoko, Wemboo Afiwa; Sondou, Essozimna; Sopoh, Ghislain Emmanuel; Kassegne, Amèwouga; Katawa, Gnatoulma; Salou, Mounerou; Karou, Simplice Damintoti; Ouendo, Edgard-Marius (Frontiers in Environmental Health, 2024)
Faced with the emergence of pandemics and the omnipresence of gaps in the process of controlling elements likely to impact the implementation of biosafety and biosecurity measures, the evaluation of the related determinants becomes an urgent necessity. The subject addressed in this study was primarily aimed at exploring the current situation of knowledge, attitudes and practices of biosafety and biosecurity as well as the associated factors in medical biology laboratories in Togo in 2021. A cross-sectional study with an analytical focus among laboratory professionals was conducted using a structured questionnaire. Statistical tests were performed using Epi Info 7.2.3.0 (2019) and Stata 13 (2013) software. Of the 322 participants, 49.1% had good knowledge while 62.4% and 77.6% had good attitudes and practices respectively. In 23.4% (25/107) of the laboratories, the staff surveyed ate their meals in the manipulation room, of which 80.0% (20/25) were in the public sector. Although the results showed that respondents who had received prior training in this area had higher score on the knowledge component (p=0.03), this intervention had no direct effect on the attitude (p=0.91) or practice (p=0.84) scores. Trained participants were significantly more likely to have good knowledge.Regional disparity was noted on the knowledge and practice components and several gaps were identified. Biosafety and biosecurity remain a challenge in medical biology laboratories in Togo.Based on the gaps identified, training, substantial improvement of the working environment, and provision of resources to achieve optimal and sustainable biosafety and biosecurity practices in Togo are required.